Off-centered leadership - Calagione, Sam (Wiley, 2016)
Off-Centered Leadership considers an innovative approach to business by exploring what happens when companies stop competing and start collaborating — both externally in the marketplace and internally in building a culture of communication, trust and alignment. Brimming with lessons on entrepreneurship and culture from the founder of Dogfish Head Craft Brewery, one of the fastest growing independent brewery in the country,members of his leadership team and external mentors from the worlds of business and art, this game-changing text turns competition on its head by showcasing how competing organizations can work together—and with other local businesses—to reach a common goal